Evaluation of Success and Failure Factors for Maternal and Child Health in Integrated Healthcare Center Information Systems (IHCIS) Using the HOT-Fit Method - Hardiyanti, Cicin; Kusumadewi, Sri; Kurniawan, Rahadian (Universitas Airlangga, 2024)
Background: Maternal and child health in Integrated Healthcare Center Information Systems (IHCIS) has been implemented in several community health centers. Some have been implemented successfully, but others have failed. Many factors influence the success and failure of IHCIS implementation. Thus, knowing these factors can be used to assist the decision-making process in implementing IHCIS. Objective: This research aims to determine the factors affecting the success and failure of IHCIS for maternal and child health using the HOT-Fit (Human, Organization, Technology, and Fit) model. Methods: This research begins with preliminary research to identify the problem, determine research variables, and collect data. It uses quantitative and qualitative approaches. A quantitative approach is conducted at locations that have successfully implemented IHCIS. The data collection instrument uses a questionnaire. A qualitative approach was conducted in locations that were still experiencing failure in implementing IHCIS. Data collection techniques through direct interviews. Results: Organizational factors do not fully determine the success or failure of the information system. Factors supporting the success of IHCIS are human (user satisfaction and system use) and technological factors (quality of information and the quality of service). However, technology (system quality and information quality) is the main factor in the failure of IHCIS implementation. Problems with system quality include the system login, limited access to the internet, and an information system that is not in accordance with requirements. The perceived information obstacle is that the system is not yet integrated, and the information produced is incomplete. Conclusion: To satisfy requirements, the information and system qualities must be enhanced. Implementing IHCIS requires an appropriate strategy according to local circumstances and conditions. This approach involves human, organizational, and technological factors. Keywords: Community Health Workers, Evaluation, HOT-Fit, Integrated Healthcare Center Information Systems, Success Factors